Estimation of renal function in adult outpatients with normal serum creatinine - Fiseha, Temesgen (BMC Res Notes, 2019)
OBJECTIVE: The aim of this study was to estimate the prevalence of renal insufficiency using estimated glomerular filtration rate (eGFR) among adult outpatients with normal SCr. RESULTS: A total of 414 patients with normal SCr were included in the study. Mean GFR (ml/min/1.73 m(2)) was 116.8 ± 43.5 using the MDRD equation and 90.5 ± 33.1 by the C–G formula. According to the MDRD formula, mild renal insufficiency (i.e. eGFR 60–89.9 ml/min/1.73 m(2)) was found in 21.5% of the patients and moderate renal insufficiency (i.e. eGFR 30–59.9 ml/min/1.73 m(2)) was found in 7.7%. According to the Cockcroft–Gault (C–G) formula, mild renal insufficiency was found in 38.2% and moderate renal insufficiency in 16.9% of the patients with normal SCr. In multivariate analysis, older age, female sex, a family history of kidney disease or other chronic diseases and high systolic blood pressure were associated with prevalent renal insufficiency depending on the formula used to estimate GFR. This study demonstrates the substantial prevalence of impaired renal function among Ethiopian adult outpatients with normal SCr. Including calculated estimates of GFR in routine laboratory reporting may help to facilitate the identification and thus optimal management of patients with renal insufficiency.